PEMBINAAN KARAKTER SANTRIWATI MELALUI FORUM ANNISA DI PONDOK PESANTREN MADINATUL MUNAWWARAH - Sintia afriyanti; Isnando Tamrin, Harmen (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2024)
Character education is one way to face challenges in the era of globalization. Character education in schools functions to develop students to have ethics, responsibility and concern, by implementing and teaching good character through an emphasis on universal values. In this era of globalization, students will be faced with external cultures that can damage students' personalities. In facing challenges, schools become a forum for strengthening the character of students in facing the flow of globalization. Strengthening character at this school can be done through positive activities, one of which is the Annisa forum. The Annisa Forum is one of the extracurricular activities at the Madinatul Munawwarah Islamic boarding school. The Annisa Forum provides materials regarding the scope of Islam, especially for women. With the studies given to female students, they can broaden their insight and strengthen their character in facing the era of globalization. In research carried out using qualitative research methods using field survey techniques.